1985
DOI: 10.1111/j.1151-2916.1985.tb10151.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of Lightweight Ceramics Based on Sintered Hollow Spheres

Abstract: Mechanical Behavior of Lightweight Ceramics Based on Sintered Hollow Spheres 395rattling in a cage, which has been suggested as the mechanism for the high microwave susceptibility of pure sodium nepheline.8 The role of the size and shape of the sample in relation to the wavelength at 2.45 GHz has yet to be studied. Also, the role of the microstructure of each gel which is dependent upon various process parameters" also needs to be investigated. Such detailed studies are under way. V. ConclusionsIt has been dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…To understand the microstructural dependence of physical properties of ceramics, especially during sintering, many models have been derived using idealized structures. 7,8 Property-porosity models based on a minimum solid area (MSA) of idealized stacking of partially sintered spherical particles were shown to agree with appropriate physical property data for bodies whose porosity is represented by such stacking. 9 -11 This paper, which builds on what is available in the literature, examines the microstructure-thermal conductivity relationship in ceramic materials, starting with the earliest stages of sintering before densification is measurable.…”
Section: Introductionmentioning
confidence: 93%
“…To understand the microstructural dependence of physical properties of ceramics, especially during sintering, many models have been derived using idealized structures. 7,8 Property-porosity models based on a minimum solid area (MSA) of idealized stacking of partially sintered spherical particles were shown to agree with appropriate physical property data for bodies whose porosity is represented by such stacking. 9 -11 This paper, which builds on what is available in the literature, examines the microstructure-thermal conductivity relationship in ceramic materials, starting with the earliest stages of sintering before densification is measurable.…”
Section: Introductionmentioning
confidence: 93%
“…It is therefore important to assess the strength and toughness of the material and to understand the physical causes which govern these properties. Recent studies [1][2][3][4][5] have led to a better understanding of these issues.…”
Section: Introductionmentioning
confidence: 99%
“…It is the case that closed cells have less heat loss due to conduction through gas, the dominant mode of heat loss [2]. Studies by these and other researchers [2,3,5] have verified that improved thermal and lightweight performance and less water absorption as well as improved compressive strength per unit weight were to be expected as a result of the substitution of closed cell spheres in place of the open cell foamed structure. The sintering of fly ash spheres to produce a closed cell microstructure for thermal insulation material has been successfully done by Briggs and also Green [3,4].…”
Section: Influence Of Microstructure On Materials Propertiesmentioning
confidence: 99%
“…In their work on sintered hollow ceramic spheres, Green and Hoagland [3] found that with close packing of spheres at higher densities, the mechanical behavior could be understood in terms of shell theory, i.e., the fracture of cell edges and the associated forces predominated and therefore imparted higher Young's modulus and compressive strength. They also found that before close packing or densification occurs, the size of the contact area or intersections of the spheres is small (see Figure 7) [3]. For these lower densities, the fracture involved failure in the immediate vicinity of a sintered contact area between two spheres.…”
Section: Influence Of Microstructure On Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation